The Effect of a 6-Month Coach Educational Program on Strengthening Coach-Athlete Interpersonal Relationships in Individual Youth Sport - Ausra Lisinskiene (MDPI AG, 2018)
The purpose of this intervention study was to develop an educational program for coaches to strengthen the coach–athlete interpersonal relationship in individual youth sport. To obtain data in the qualitative interpretative phenomenology phase, 10 youth sports coaches took part in semi-structured, in-depth interviews. The educational program was developed by integrating psychological, educational and social skills into the educational coaching sessions. The program involved a detailed video analysis, theoretical classes, and individual consultations. The qualitative interpretative phenomenology research design was used and enabled to evaluate the program. The study results revealed that the program had a positive impact on the transformation of the coach–athlete interpersonal relationship in sport. Behavioural, emotional, cognitive, and social strategies changes occured. The quality of the coach–athlete relationship changed: trust, communication, cooperation, encouragement, and a connection between athletes and the coaches appeared. The study’s results showed that the educational program for coaches had a positive effect on the quality of interpersonal relationships between athletes and the coaches and increased positive coaching strategies in youth sport.